Perbedaan infrastruktur pendidikan antara pedesaan dan perkotaan: Dampaknya terhadap kualitas pembelajaran - Zuqria, Lailatul (Maliki Interdisciplinary Journal, 2026)
This study This study aims to analyze the differences in educational infrastructure between rural and urban areas and their impact on the quality of learning. Adequate educational infrastructure is considered one of the key factors in supporting an effective teaching and learning process. The study employed a quantitative approach using a survey method involving a number of schools in both rural and urban areas as samples. Data were collected through questionnaires measuring physical facilities, access to technology, number of educators, and other supporting infrastructure. The findings indicate significant differences in educational infrastructure between rural and urban areas, where urban schools tend to have more comprehensive facilities and better access to technology. These disparities clearly affect the quality of learning, as urban schools demonstrate better outcomes in terms of academic achievement and student skill development. Conversely, rural schools face limitations in infrastructure that hinder the effectiveness of teaching and learning. The study recommends the need for equitable development of educational infrastructure across all regions in order to improve the overall quality of education in Indonesia.